Immunological Response Against SARS-COV-2 After BNT162b2 Vaccine Administration Is Impaired in Allogeneic but Not in Autologous Stem Cell Transplant Recipients - Chiarucci, Martina; Paolasini, Sara; Isidori, Alessandro; Guiducci, Barbara; Loscocco, Federica; Capalbo, Maria; Visani, Giuseppe (Frontiers in Oncology, 2021)
The efficacy of Covid-19 vaccine in hematopoietic stem cell transplantation (HSCT) recipients is still unknown. We planned a prospective study to evaluate the immune response after the administration of Covid-19 vaccine in HSCT recipients. Fifty patients previously submitted to HSCT (38 autologous and 12 allogeneic) received the mRNA-based SARS-CoV-2 vaccine BNT162b2 (Pfizer-BioNTech). Serum samples of all patients were tested for SARS-CoV-2 IgG against the Spike glycoprotein, 30 days after the second dose of vaccine. Antibody response was compared to a control group of 45 healthy subjects. Of the 50 patients tested, 12 did not develop any antibody response, including 6 patients undergoing autologous (16%) and 6 allogeneic HSCT (50%). Cyclosporine administration in allogeneic recipients and prior administration of Rituximab in the autologous setting correlated with lower antibody titers (p < 0.0003 and p=0.000, respectively). Flow cytometry of peripheral blood samples, performed 30 days after the vaccination, showed a significant correlation between the antibody response to Sars-COV2 and an increased number in CD19+ B lymphocytes (p = 0.0003) and CD56+ natural killer (NK) cells (p = 0.00). In conclusion, prior Rituximab before autologous HSCT and cyclosporine administration after allogeneic HSCT negatively affected the antibody response to Sars-COV2 vaccine, possibly due to their immunosuppressive action on CD20 +B cells and T cells, respectively. The correlation between seroconversion to Sars-COV2 and higher number of CD19 + B cells and CD56+ NK cells, suggests a central role for B and NK cells in the development of COVID-19 immunity after vaccination with a mRNA-based platform.